2000
DOI: 10.1038/35012108
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the plant gene MOM releases transcriptional silencing of methylated genes

Abstract: Epigenetic modifications change transcription patterns in multicellular organisms to achieve tissue-specific gene expression and inactivate alien DNA such as transposons or transgenes. In plants and animals, DNA methylation is involved in heritability and flexibility of epigenetic states, although its function is far from clear. We have isolated an Arabidopsis gene, MOM, whose product is required for the maintenance of transcriptional gene silencing. Mutation of this gene or depletion of its transcript by expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
262
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 248 publications
(271 citation statements)
references
References 30 publications
9
262
0
Order By: Relevance
“…Given that DNA methylation has not been reported at the FLC locus, it appears that DNA methylation is not a requirement for the recruitment of FPA and possibly other AP components. It is worth noting that the activation of methylated loci without a reduction in DNA methylation is not unprecedented; morpheus' molecule1 mutations lead to the activation of methylated loci without affecting DNA methylation (Amedeo et al, 2000). Thus, processes downstream of DNA methylation are required for transcriptional silencing, and the AP may play a role in this process.…”
Section: Discussionmentioning
confidence: 99%
“…Given that DNA methylation has not been reported at the FLC locus, it appears that DNA methylation is not a requirement for the recruitment of FPA and possibly other AP components. It is worth noting that the activation of methylated loci without a reduction in DNA methylation is not unprecedented; morpheus' molecule1 mutations lead to the activation of methylated loci without affecting DNA methylation (Amedeo et al, 2000). Thus, processes downstream of DNA methylation are required for transcriptional silencing, and the AP may play a role in this process.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Lembo et al (36) recently reported that MBDin, a regulatory factor of MBD2, reversed MBD2-mediated transcriptional repression from a methylated promoter by binding with the COOHterminal region of MBD2. Another example of antisilencing without DNA demethylation has been shown in plants (37). MOM is an Arabidopsis gene that has been found to be important in maintaining gene silencing in a methylation-independent fashion.…”
Section: Discussionmentioning
confidence: 99%
“…Like DDM1, the MORPHEUS MOLECULE (MOM) gene also encodes a SWI/SNF-like protein that, similar to DDM1, can also release transcriptional gene silencing. However, in contrast to ddm1 mutants in mom mutants, no changes in DNA methylation have been observed (Amedeo et al 2000). To address the question of whether the mom mu- tation could also modify PHE1 expression in an mea mutant background, we analyzed PHE1 mRNA levels by real-time PCR in mea/MEA; mom/mom double-mutant plants (F3 generation) during different stages of seed development.…”
Section: Phe1ϻgus Is Expressed In the Absence Of Fertilization In Fiementioning
confidence: 99%